A mid- and long-term follow-up study on the bilateral pedicle anchoring technique with percutaneous vertebroplasty for the treatment of Kümmell's disease - Dai, Shichang; Du, Yu; Chen, Liang; Xu, Yifan; Hu, Qiong (Frontiers in Surgery, 2023)
OBJECTIVE: To investigate the clinical efficacy and long-term stability of bone cement of bilateral pedicle anchoring technique with percutaneous vertebroplasty in the treatment of Kümmell disease. METHODS: From January 2016 to January 2019, 41 patients with Kümmell disease treated by bilateral pedicle anchoring technique with PVP in our hospital were collected. There were 10 males and 31 females with an average age of 76.5 ± 8.0 years (range, 55-92 years). The average period of follow-up was 19.3±8.0 months (range, 12-38 months). The visual analogue scale (VAS) scores, Oswestry disability index (ODI), Anterior vertebral height, Kyphotic angle, and Wedge angle were recorded before operation, 1 day after operation, and last follow-up. The clinical efficacy, vertebral height recovery, and bone cement displacement were analyzed in combination with X ⁃ ray film, CT, MRI and other imaging data. RESULTS: All patients successfully underwent the procedure without serious complications. No obvious displacement of bone cement was found in the imaging data from 1 day after operation and last follow-up. The VAS scores, ODI scores, anterior vertebral height, kyphotic angle, and wedge angle of the injured vertebrae were significantly improved after surgery. There was no significant difference in the anterior vertebral height, kyphotic angle, and wedge angle of the vertebral body at 1 day after operation and the last follow-up. Bone cement leakage occurred in seven patients, and no abnormal clinical symptoms. CONCLUSION: The bilateral pedicle anchoring technique with PVP integrates the bone cement in the vertebral body and the bone cement in the pedicle, enhances the stability of the bone cement, and effectively prevents the displacement of the intravertebral bone cement. The postoperative bone cement stability is high, the clinical effect is obvious and long-term Follow-up results are satisfactory. It is a safe and effective surgical method for the treatment of Kümmell disease.